Emotional Accompaniment of the Organization of Time Perspective of Forced Ukrainian Migrants Staying Abroad - Plokhikh , Viktor; Kireieva Zoіa; Skoromna , Marianna (Insight: the psychological dimensions of society, 2024)
The аim. Determination of the specificity of a correlation between the organization of time perspective and emotional experiences of forced Ukrainian migrants staying abroad in terms of their orientation toward adaptation in a critical situation of life activity. Methods. 77 forced Ukrainian migrants in the countries of Europe and North America (aged from 19 to 48 years) were research participants. The following instruments were used in the research: “Time Perspective Inventory” P. Zimbardo; “Differential Emotions Scale” C. Izard; The Freiburg Personality Inventory (FPI, Form В); the method of C. Spielberger for determining the level of personal and reactive anxiety; the scale “time competence” of the self-actualization test by Е. Shostrom. Results. It was found that the indicators of acute negative emotions (Me = 27.00) and personal anxiety (Me = 45.00) are high in the researched participants. The Friedman test allowed identifying statistical differences in the intensity of manifestations of different emotions in the total sample (χ2 = 33,693; df = 9; p < .001) through the most expressive emotion of interest (Me = 8.00). It was established that manifestations of emotions have statistical correlations with time perspectives in the following way: interest with the negative past (rs = -.294; p = .009), the hedonistic present (rs = -.264; p = .020) and the future (rs = .376; p = .001); anger with the negative past (rs = .499; p < .001), the hedonistic present (rs = .266; p = .019) and the fatalistic present (rs = .228; p = .046); contempt with the negative past (rs = .427; p < .001) and the future (rs = -.321; p = .004). It was also found that anxiety correlates with time perspective in the following way: reactive anxiety with the negative past (rs = .319; p = .005) and the future (rs = -.234; p = .041); personal anxiety with the negative past (rs = .452; p < .001) and the future (rs = -.251; p = .027). Discussion and conclusions. The degree of expressiveness of negative emotions and personal anxiety in forced Ukrainian migrants staying abroad prevents efficient determination of the future perspective and results in proneness to a fatalistic attitude towards the current circumstances. The researched migrants’ increased orientation towards the current hedonistic satisfaction of their needs does not contribute to adaptation and correlates with expressive negative experiences of the past and present circumstances and restricts determination of the future perspective. High expressiveness of the emotion of interest contributes to evident adaptation-based orientation of forced migrants towards eliminating uncertainty of the future perspective.